ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN SABUN PEMBERSIH WAJAH MERK - Wati, Anna Firinda; Tjahjono, Endro; Mulyati, Awin (Jurnal Dinamika Administrasi Bisnis, 2015)
The aim of research to determine the factors that influence purchasing decisions soap brand Pond's facial cleanser along with the dominant factor. The independent variable in this research is Price (X1), Ad (X2), Packaging (X3), and Quality (X4). The dependent variable is the purchase decision (Y)., The research sample was determined at 100 students. Sampling method in this research using accidental sampling method. Techniques using multiple linear regression analysis.From the test results obtained simultaneously variable pricing, advertising, packaging and quality have an influence on purchasing decisions soap cleanser brand Pond's, whereas packaging has no significant influence on purchasing decisionsÂ Keywords: Pricing, Advertising, Packaging, Quality and Purchasing Decision